Optimasi Propilen Glikol dan Etanol sebagai Peningkat Penetrasi Ibuprofen dalam Sediaan Gel dengan Metode Simplex Lattice Design (Propylene Glycol and Ethanol Optimization as Ibuprofen Penetration Enhancer in Gel Dosage using Simplex Lattice Design Metho - Baiq Wahyudyati Karnia Qisti; Dwi Nurahmanto; Viddy Agustian Rosyidi (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Ibuprofen is a non-steroid anti inflammatory drug (NSAID) used for rheumatoid arthritis treatment. In this study, formulation, evaluation, and optimization of ibuprofen gel formula were conducted in order to determine the best ibuprofen penetration rate through the rats skin using propylene glycol and ethanol as penetration enhancers and to find out the optimum formula to get the best penetration rate with simplex lattice design method. Evaluations included organoleptic, pH, viscosity, gel dispersive, assay of gel formulations, and ibuprofen penetration rate assay. Penetration rate was determined by paddle type dissolution and the samples were analyzed by spectrophotometry UV-Vis. The results of ibuprofen penetration rate assay were analyzed and optimized using design expert trial version 10. The results of ibuprofen penetration rate were F1 1.524 ± 0.121 µg/cm2.minute; F2 1.945 ± 0.0104 µg/cm2.minute; and F3 1.173 ± 0.216 µg/cm2.minute. Penetration rate optimization resulted in one optimum solution formula which was 18.000% propylene glycol and 12.000% ethanol with a maximum flux of 1.957 ug/cm2.minute and desirability 1. It can be concluded that the best ibuprofen penetration rate was F2 with flux 1.945 ± 0.0104 µg/cm2.minute with 15% propylene glycol and 15% ethanol. Keywords: gel, ibuprofen, propylene glycol, ethanol, simplex lattice design